2017
DOI: 10.1071/bt17152
|View full text |Cite
|
Sign up to set email alerts
|

Unassisted invasions: understanding and responding to Australia’s high-impact environmental grass weeds

Abstract: Abstract. Alien grass species have been intentionally introduced into Australia since European settlement over 200 years ago, with many subsequently becoming weeds of natural environments. We have identified the subset of these weeds that have invaded and become dominant in environmentally important areas in the absence of modern anthropogenic disturbance, calling them 'high-impact species'. We also examined why these high-impact species were successful, and what that might mean for management. Seventeen high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…A similarity of long lag phases in trees and grasses, despite differences in life form and generation time is thus perplexing (see also Sutherland 2004). It is plausible that because members of both groups were intensely introduced simultaneously in late 19th and early twentieth centuries (Cook and Dias 2006;van Klinken and Friedel 2018), the subset of introduced grass species that evolved with time to become high impact invaders (e.g. grader grass [Themeda quadrivalvis], hymenachne [Hymenachne amplexicaulis] and Aleman grass [Echinochloa polystachia]) have followed similar high spread trajectories as that of the trees-seemingly encouraged by ecological novelty (unprecedented human-mediated changes at different ecological levels), high propagule pressure and ability to respond to and even alter natural disturbances of fire and inundation (van Klinken and Friedel 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A similarity of long lag phases in trees and grasses, despite differences in life form and generation time is thus perplexing (see also Sutherland 2004). It is plausible that because members of both groups were intensely introduced simultaneously in late 19th and early twentieth centuries (Cook and Dias 2006;van Klinken and Friedel 2018), the subset of introduced grass species that evolved with time to become high impact invaders (e.g. grader grass [Themeda quadrivalvis], hymenachne [Hymenachne amplexicaulis] and Aleman grass [Echinochloa polystachia]) have followed similar high spread trajectories as that of the trees-seemingly encouraged by ecological novelty (unprecedented human-mediated changes at different ecological levels), high propagule pressure and ability to respond to and even alter natural disturbances of fire and inundation (van Klinken and Friedel 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Non‐native grasses in general threaten the integrity of vast areas of Australia (Firn et al., 2015; van Klinken & Friedel, 2018), yet their control and the recognition of their impact represents a chronic policy failure (Downey et al., 2010; Godfree et al., 2017). Unlike other key threats that have largely realized their potential ranges and impacts, buffel continues to rapidly spread beyond the 68% of the continent previously considered suitable for its establishment (Lawson, Bryant, & Franks, 2004) as evidenced by its invasion of new habitats and climates (Hobbs, Naby, & Schutz, 2015; Tschirner, Gibbs, & Heap, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas other serious weeds of central Australia, like Tamarix aphylla and Parkinsonia aculeata, are outcompeted by established natural vegetation or are largely restricted to agricultural or disturbed areas with enhanced water or nutrient availability (Grice & Martin, 2006), buffel is an aggressive invader of many Australian arid and semi‐arid zone habitats (Fensham, Wang, & Kilgour, 2015; Firn et al., 2015; van Klinken & Friedel, 2018). Buffel directly suppresses (Abella, Chiquoine, & Backer, 2012; Eilts & Huxman, 2013) and threatens the persistence of many native plants (Clarke et al, 2005; Edwards, Schlesinger, Ooi, French, & Gooden, 2019; Eyre, Wang, Venz, Chilcott, & Whish, 2009; Fairfax & Fensham, 2000; Friedel et al., 2006) including threatened species (Griffin, 1993; Jackson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Following these assessments, it was not included in the top 32 but was still deemed to be a significant threat to Australian biodiversity (Navie and Adkins, 2007). A recent study by Van Klinken and Friedel (2017) found that E. curvula within Australia is a high impact species but only in the localised communities where it is found, not nation- (Csurhes et al, 2016;Sharp, 2011). For Queensland and Northern Territory, it is not prohibited but there is a general biosecurity duty to remove and eliminate the species where practical to minimise any potential spread (Csurhes et al, 2016).…”
Section: Australiamentioning
confidence: 99%
“…Following these assessments, it was not included in the top 32 but was still deemed to be a significant threat to Australian biodiversity (Navie and Adkins, 2007). A recent study by Van Klinken and Friedel (2017) found that E. curvula within Australia is a high impact species but only in the localised communities where it is found, not nationally. The management of the species is mandated by the relevant state or territory government within Australia.…”
Section: Distribution Habitat and Current Management Of Eragrostis Curvulamentioning
confidence: 99%